2019
DOI: 10.1186/s12881-019-0793-z
|View full text |Cite
|
Sign up to set email alerts
|

A case report of recessive restrictive cardiomyopathy caused by a novel mutation in cardiac troponin I (TNNI3)

Abstract: Background Restrictive cardiomyopathy is a rare cardiac disease, for which several genes including TNNT2 , MYPN , FLNC and TNNI3 have been associated with its familial form. Case presentation Here we describe a female proband with a severely manifested restrictive phenotype leading to heart transplantation at the age of 41, who was found homozygous for the novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In 2018 Streff et al [ 32 ] reported a complex phenotype, characterized by the co-occurrence of early onset DCM together with Amish nemaline myopathy, in a child carrying a homozygous contiguous gene deletion of about 11 kb, which encompassed the last exon of TNNI3 . Another biallelic variant, although in relation to a remarkably different cardiac phenotype, was published in 2019, when Pantou et al [ 33 ] identified a homozygous p.(Asp196His) substitution in three adult siblings, two of them suffering from late onset RCM and one from HCM, while heterozygous carriers in the family were apparently healthy. Kühnisch et al [ 28 ] further widened the phenotypic and genotypic spectrum by identifying two unrelated pediatric patients, one with early onset DCM and the other with a familial form of LVNC, carrying homozygous p.Arg69Alafs* and c.24+2T>A p.(?)…”
Section: Discussionmentioning
confidence: 99%
“…In 2018 Streff et al [ 32 ] reported a complex phenotype, characterized by the co-occurrence of early onset DCM together with Amish nemaline myopathy, in a child carrying a homozygous contiguous gene deletion of about 11 kb, which encompassed the last exon of TNNI3 . Another biallelic variant, although in relation to a remarkably different cardiac phenotype, was published in 2019, when Pantou et al [ 33 ] identified a homozygous p.(Asp196His) substitution in three adult siblings, two of them suffering from late onset RCM and one from HCM, while heterozygous carriers in the family were apparently healthy. Kühnisch et al [ 28 ] further widened the phenotypic and genotypic spectrum by identifying two unrelated pediatric patients, one with early onset DCM and the other with a familial form of LVNC, carrying homozygous p.Arg69Alafs* and c.24+2T>A p.(?)…”
Section: Discussionmentioning
confidence: 99%
“…Several gene mutations have been recognized as a cause of RCM and TNNI3 seems to be the most prevalent disease gene in RCM ( Figure 3 ). 2 , 3 , 5 , 8 , 11–14 …”
Section: Discussionmentioning
confidence: 99%
“…endomyocardial fibrosis) forms. 2 , 3 Mutations in sarcomeric and cytoskeletal genes, amongst them the troponin complex subunits T ( TNNT2 Troponin T) 4 and I ( TNNI3 Troponin I), 5 have been associated with hereditary RCM.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac troponin I is highly specific for heart muscle and higher concentrations in the blood are associated with higher general in-hospital mortality for a number of illnesses (25). It serves as a sensor of intracellular calcium, regulating the interaction between thick and thin sarcomere filaments during the heart muscle contraction (26). We hypothesise that this protein may be relevant to COVID-19 as ∼40% of deaths in a cohort from Wuhan (27) were attributed to myocardial damage and heart failure, as well as increased mortality in individuals with both COVID-19 and acute cardiac injury (28).…”
Section: Discussionmentioning
confidence: 99%